2019
DOI: 10.1108/arch-12-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Architecture, urban form, and assemblage aesthetics in Mexico City’s street markets

Abstract: Purpose The purpose of this paper is to consider Mexico City’s street markets as temporary and modular architectural products that emerge out of intensive, routine and repeated negotiations over urban spatial affordances in a crowded metropolitan environment. Particular attention is given to the polychromatic visual form, not as some detached work of art, but as a collection of tiny signals of the labor, commerce and social relations unfolding below. Design/methodology/approach For this paper, the author has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…At an urban scale, a number of papers explore the multilayered nature of the urban condition. Heathcott’s (2019) work examines the everyday street market environment in Mexico City. Identifying five spatial typologies of street markets, including the linear, the circuit, the cluster, the contour and the hybrid, his work divulges the polychromatic markets as expressions of an assemblage aesthetic involving cumulative daily choices, desires, routines and densely intertwined associations of working-class individuals and communities.…”
Section: Seven Themes Shaping Diversity Of Research Endeavorsmentioning
confidence: 99%
“…At an urban scale, a number of papers explore the multilayered nature of the urban condition. Heathcott’s (2019) work examines the everyday street market environment in Mexico City. Identifying five spatial typologies of street markets, including the linear, the circuit, the cluster, the contour and the hybrid, his work divulges the polychromatic markets as expressions of an assemblage aesthetic involving cumulative daily choices, desires, routines and densely intertwined associations of working-class individuals and communities.…”
Section: Seven Themes Shaping Diversity Of Research Endeavorsmentioning
confidence: 99%
“…The second workday stearic acid decrease is difficult to explain because of several physicochemical changes during deep-frying as oil absorption by food and fatty acid transfer into the oil (Torres & Rojas, 2018;Dobarganes & Márquez-Ruiz, 2015;Sayon-Orea et al, 2015). It should be mentioned that the present research has shown real food vendor condition operations, identified in Mexican traditional markets (Tianguis), which are a common food offer practice in Metropolitan areas in Mexico (Espinoza-Ortega et al, 2016;Heathcott, 2019;Lozano et al, 2019). These kinds of vendors workday's real conditions effects were studied; otherwise, the related reports based on controlled frying conditions (Temperature or one kind of food processed, mainly) presented higher fatty acid oil deterioration degrees, but at higher temperatures and with no edible vegetable oil mix (Marinova et al, 2012).…”
Section: Fatty Acid Composition Analysis By Gas Chromatography (Fac)mentioning
confidence: 73%
“…Toluca Valley and Mexico City shown some market type named Tianguis, which are temporary and informal street markets, where one of their higher sales is food. Food street vendors around America Latina are not always observed by health government authorities; therefore, obesogenic intake is freely sold (Carrete & Arroyo, 2014;Heathcott, 2019;Lozano et al, 2019). Street fast food is a representative culinary endemic menu and an important viable food alternative for workers, who are not able to go home for lunch because of distance, lack of resources, or traveling time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The space of the public realm and assessment of designed environments The knowledge space addressing the public realm and assessment studies of built environments (building and urban environments) seems to be very well-established given the intensity of contributions which vary in purpose, scope, scale and approach to investigation. Examples of recent contributions include the work of Heathcott (2019) which places emphasis on polychromatic visual form in examining the temporality and modularity of Mexico City's street markets; the work of Azzali (2020) which identifies best practices and successful examples used during and after mega-events, in the contexts of London, Sochi and Rio de Janeiro, to transform event sites and venues into livable public open spaces (POSs) that contribute to a vibrant city life; the work of Hollander and Anderson (2020) which explores the relationship between urban facades and affective feelings through an empirical study that responds to the question of how do people perceive edge conditions in urban environments; and the work of Vukovic et al (2021) which adopts a quality of urban life perspective in the structured assessment of three POSs in Belgrade. Notably, key contributions that advance methods or expand the boundaries of the knowledge space include the work of Drista and Biloria (2021) which articulates a critical review of studies that map the urban environment using continuous physiological data collection and concludes with conceptual model that aims to mitigate urban stress at the city and the user levels; and more recently the work of (Tahroodi and Ujang, 2021) which establishes an understanding of the interrelations between the visual and physical accessibility attributes of path structure and their impacts on the intensity of passive social interaction across urban parks in Kuala Lumpur, Malaysia.…”
Section: 2mentioning
confidence: 99%